A sociological analysis of the lives and livelihoods of child support grant caregivers in Queenstown, South Africa - Ntantiso, Ziyanda (Rhodes University, Faculty of Humanities, Department of Sociology, 2017)
The post-apartheid state in South Africa has initiated and implemented a large-scale social assistance programme in the form of social grants, including the child support grant. The grant system is meant to provide recipients, who comprise mainly people from poor black households, with the capacity to reduce levels of poverty in their households. The grant with the largest number of recipients is the child support grant, and it is given to the caregiver of a child eligible to receive the grant. Though the value of the monthly grant is minimal, the prevailing literature suggests that it does contribute in some way to enhancing the welfare of the recipients. This thesis focuses on child support grant recipients in the town of Queenstown in the Eastern Cape, and particularly those recipients for whom the grant is the crucial source of income. The main objective of the thesis is to understand and analyse the lives and livelihoods of child support grant recipients (all women) in Queenstown, South Africa. In this regard, the vast majority of caregivers of grant children are women and they often rely exclusively on the grant in taking care of themselves and the children. The thesis does not seek to determine any direct causal relationship between the child grant and poverty reduction, as much of the existing literature seeks to do. It focuses instead on the lives of the grant recipients, including the many challenges they face, as well as how they use the grant to pursue livelihoods in a manner which may at least inhibit the prospects of entering into deeper levels of poverty. The thesis demonstrates that, despite their deprived conditions of material existence, the female caregivers in Queenstown display significant agency in caring for their grant children.
Keywords: Uncatalogued